The role of stakeholders and partners in the effective managemnt of education for sustainable development in Africa (2009)
This paper examines some roles played by different stakeholders and partners in their effeorts to use quality education for sustainable development (ESD) as was initiated by the United Nationa Organization. Education for sustainable development is a vision that seeks to utilize education to empower people to assume responsibility for creating a sustainable future. A central issue to ESD is the concept of culture, an essential underlying theme. It has been acknowledged by experts that there is no single route to sustainable development. Yet, it is obviously acknowledged that education and perhaps research are the most tools for accomplishing sustainable development. Invariably, there are quite a number of different stakeholders in the enterprise of sustainable development. Each stakeholders has a different vision of sustainable development and how it can contribute to its sustenance. While some are interested in enviromental presevation and protection, some have economic development interests while others may be interested in social development. The challenges of this paper therefore is to articulate the various roles and responsibilities being played by these stakeholders with a view to creating synergies and partnerships among them in ensuring an enduring ESD.